Local Government Policy Regarding Mandatory Students Diniyah Takmiliyah in Indramayu Regency - Umar Sidiq; Afiful Ikhwan (Karsa: Journal of Social and Islamic Culture, 2018)
Indramayu District Government issued Local Regulation No. 12 of 2012 on Compulsory Education Diniyah Takmiliyah. Compulsory Education Diniyah Takmiliyah is a Non-Formal Religious Education Program which must be followed by all students starting from elementary level up to upper level in Indramayu District on joint responsibility between local government and province and society. Diniyah Takmiliyah aims to complement the Islamic religious education obtained at the basic level up to the upper level or in higher education in order to increase the faith and devotion of learners. This study uses qualitative analysis of case studies. The results of this study are expected to be useful and contribute thoughts to other local governments to implement compulsory diniyah policy. This research explains the background of the birth of the regulation of Indramayu Regency about the compulsory education of Diniyah Takmiliyah from the community; also describes the strategy implementation strategy from concept, set into local regulations, followed by regent regulation, socialization and control; as well as describe the implications experienced in the implementation of this policy such as increasing the achievement of Islamic studies in schools, the addition of religious lessons, the local budget for Islamic education, the increase of Madrasahs in the study sites and the effect of political electability decision makers.